Realisasi Kesantunan Tindak Tutur Antara Mahasiswa dan Dosen dalam Interaksi Verbal di Universitas Surakarta - Susylowati, Eka; Yulianti, Wiwik; Agung Ayu Dian Andriyani, Anak; Wisudawanto, Rahmat (Yayasan Arrahman Nahdlatul Wathan, 2023)
The purpose of this study is to find out the forms of speech acts between lecturers and students at Surakarta University in the verbal interactions in Surakarta University. The data in this study namely student and lecturer speech in teaching-learning interactions and outside teaching-learning interactions. Data collection was carried out by means of observation, interviews and notes. The results of this study indicate that the University of Surakarta includes locutionary, illocutionary, and perlocutionary speech acts. The most frequently occurring speech act is the illocutionary act which includes directives. The pragmatic power contained in conversations between lecturers and students in verbal interactions is realized through directive speech acts. The pragmatic powers found in the study including giving information, ordering, suggesting, praising and challenging.